Evaluation of the effect of nano‐graphene oxide on shear bond strength of conventional and resin‐modified glass ionomer cement - Parisa Ghodrati; Farahnaz Sharafeddin (Wiley, 2023)
Abstract Objectives Recently, nano‐graphene oxide (nGO), a material with unique mechanical properties, has been introduced to improve the properties of glass ionomer cement (GIC). The purpose of this study was to investigate the effect of adding nGO on the shear bond strength (SBS) of conventional (CGIC) and resin‐modified GIC (RMGIC). Methods Sixty intact molars were mounted and their occlusal surface was cut at a depth of 1 mm below the dentinoenamel junction. 1 wt.% and 2 wt.% of nGO (US Research Nanomaterials, Inc.) were added to CGIC and RMGIC (GC Corporation). The samples were randomly divided into six groups (n = 10), including 1: CGIC,  2: CGIC + 1% GO, 3: CGIC + 2% GO, 4: RMGIC, 5: RMGIC + 1% GO, and 6: RMGIC + 2% GO. Plastic molds were placed on the surface of the dentin pretreated with 10% polyacrylic acid (GC Corporation) and filled with prepared cement according to the manufacturer's instruction. After 24 h of storage in an incubator, the SBS test was done by the universal testing machine. Data were analyzed using two‐way analysis of variance and post hoc Tukey tests (p < .05). Results In the group of CGIC, mean SBS was significantly lower than all other study groups (p < .001), and groups 5 (RMGIC + 1% GO) and 6 (RMGIC + 2% GO) showed significantly higher values compared to all other study groups (p < .001). However, the difference between groups 2 and 3, as well as the difference between groups 5 and 6, was not significant (p = .999 andp = .994, respectively). RMGI groups had significantly higher SBS than their corresponding CGIC groups. Conclusions The addition of 1% and 2% nGO significantly increased the SBS of CGIC and RMGIC to the dentin, which can be considered as a promising point for wider clinical application of this material.